2014
DOI: 10.1186/bf03352467
|View full text |Cite
|
Sign up to set email alerts
|

Local time dependence of the frequency of Pi2 waves simultaneously observed at 5 low-latitude stations

Abstract: One-second resolution geomagnetic data from 5 stations located at low-latitudes (i.e., L = 1.2 ∼ 1.6) were used to examine the local time dependence of the dominant frequency of Pi2 pulsations. We analyzed 183 Pi2 events simultaneously recorded at the 5 stations and discussed their possible generation mechanisms. The averaged dominant frequency of the H (horizontal) component is higher on the dawn side than that on the dusk side and shows a peak value in the post-midnight at around 03 LT, which confirms the LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
5
16
0
Order By: Relevance
“…From simultaneous observations with 5 low-latitude (L=1.2-1.6) stations in Japan and China, Han et al (2003) found the similar LT dependence of frequency of nightside Pi2 pulsations. Fujita and Itonaga (2003) reproduced this LT dependence of Pi2 frequency by a numerical simulation of the plasmaspheric cavity resonance (or the plasmaspheric virtual resonance), where longitudinal non-uniformity was introduced in the plasmaspheric Alfvén velocity.…”
Section: Pi2 Pulsations With Different Periods Betweenmentioning
confidence: 84%
See 2 more Smart Citations
“…From simultaneous observations with 5 low-latitude (L=1.2-1.6) stations in Japan and China, Han et al (2003) found the similar LT dependence of frequency of nightside Pi2 pulsations. Fujita and Itonaga (2003) reproduced this LT dependence of Pi2 frequency by a numerical simulation of the plasmaspheric cavity resonance (or the plasmaspheric virtual resonance), where longitudinal non-uniformity was introduced in the plasmaspheric Alfvén velocity.…”
Section: Pi2 Pulsations With Different Periods Betweenmentioning
confidence: 84%
“…Therefore satellites in the low L shell (mostly less than L∼5) observe the geomagnetic field oscillations predominantly in the compressional and radial components when substorms occur (Lin and Cahill, 1975;Sakurai and McPherron, 1983;Takahashi et al, 1995Takahashi et al, , 1999aKeiling et al, 2001;Kim et al, 2001). Polar orbiting satellites in low Earth orbit (450-850 km altitude) also detect compressional oscillations that are correlated with lowlatitude Pi2 pulsations on the nightside (Takahashi et al, 1999b;Sutcliffe and Lühr, 2003;Han et al, 2004). Studies that compare magnetometer data from low-latitude ground stations and the CRRES satellite staying inside the plasmasphere revealed radial structure of the fundamental plasmaspheric cavity mode on the nightside (Takahashi et al, , 2003a.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another observational aspect of low-latitude Pi2 pulsations that differs from the simple PCR model is the spatial variation of the Pi2 frequency within the plasmasphere, both with longitude (Kosaka et al 2002;Han et al 2003) and latitude (Kim et al 2005a). The variation contradicts the simple PCR model, which predicts a mode that oscillates at the same frequency anywhere in the plasmasphere (note that there are other studies indicating that the Pi2 frequency does not depend on longitude, e.g., Sutcliffe and Yumoto (1989) and Nosé et al (2006)).…”
Section: Periodmentioning
confidence: 98%
“…However, they also found a small number of Pi2 pulsations which have small phase differences corresponding to |m| ∼0.24-0.48. Kosaka et al (2002) and Han et al (2003) reported that the dominant frequency of mid-and low-latitude Pi2 pulsations depends on the local time. It is therefore important to examine the longitudinal dependence of low-latitude Pi2 pulsations' characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%